Development of log management system in CoolView - Kai-shuo XU; Hua YUAN (Tongxin xuebao)
In order to realize the normalized management of the tasks such as auditing,tracking and warning in video conference system.A log management subsystem structure was built using AOP.Its log module adopting Syslog and Log4j technology was designed,and using SSH framework was implemented.The above subsystem also has been enbe-ded in CoolView video conference system,and it provides foundation data for daily operation and maintenance of CoolView.